Achieving Better Benefits via Flexible Feature Matching in Post-Deduplication Delta Compression - Yang, Fengkui; Mao, Bo; Liu, Yuhan; Bao, Liang; Jiang, Weipeng; Zhang, Dongying; Li, Chunhua; Zhou, Ke (Proceedings - IEEE International Parallel and Distributed Processing Symposium, 2025)
Cloud or distributed storage systems characterized by high data redundancy necessitate effective data reduction techniques to reduce storage costs. Post-deduplication delta compression has proven effective by eliminating both duplicated and similar yet non-duplicated chunks. However, existing approaches often rely on fixed-feature matching for resemblance detection, which, while fast, may lead to lower reduction ratios and not robust benefits across various datasets. In this paper, we introduce BePro, a novel system that integrates Flexible Feature Matching (§IV-A) to achieve better benefits in post-deduplication delta compression. BePro employs Gain Filtering (§IV-B) to identify high-gain chunks while discarding low-gain similar chunks, ensuring robust benefits across different datasets. Additionally, BePro implements a new indexing structure, LSH-Delta (§IV-C), to search for similar chunks and utilizes Index Load Balancer (§IV-D) for efficient resemblance detection by exploiting the distribution characteristics of similar chunks. Furthermore, the Index Manager (§IV-E) skillfully manages memory space overhead, ensuring memory efficiency. We implemented a pipeline prototyping framework to facilitate the evaluation of BePro and other leading techniques. Extensive experiments demonstrate that BePro improves the data-reduction ratios by up to 1.15 ×-2.35 × while achieving comparable speed.